If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + -3 + -11b + -9 = 0 Reorder the terms: -3 + -9 + 2b + -11b = 0 Combine like terms: -3 + -9 = -12 -12 + 2b + -11b = 0 Combine like terms: 2b + -11b = -9b -12 + -9b = 0 Solving -12 + -9b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -9b = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -9b = 0 + 12 -9b = 0 + 12 Combine like terms: 0 + 12 = 12 -9b = 12 Divide each side by '-9'. b = -1.333333333 Simplifying b = -1.333333333
| (200000-X)*0.2=80000-X | | x/35=60/100 | | x/250=108/100 | | a^2x^2+abx-2b=0 | | 7(a+8)=63 | | 76+x=82+y | | 11x/12+5/12=x-2 | | 76+x=82+x | | X^2-6x-9=7 | | (a+b)(3ab+b^2)=0 | | 3m+5=12-m | | 8-q=10 | | 5(3h-2)=4-12r | | x/10=9 | | 6x-4=4x+12 | | 4=x/6 | | 10x^2+2x-4=0 | | 2x^4+5x^2-207=0 | | 10x+2x-4=0 | | 4e^7x=8 | | 0=-16t^2+328 | | 4x^2-24x+5=0 | | x^4-3x^2=4 | | 3x^3+x^2-21x+14=0 | | 2v=0 | | 8=x/7 | | 3+10x-2=4x-12+16 | | 4-2x=5-3(x-1) | | 4-2x=5-3 | | 21x^2-25x=4 | | (x+y+1)dx+(2x+2y-1)dy=0 | | 3b-4c=10 |